Pengaruh Pemberian Telur Rebus Ayam Kampung Terhadap Peningkatan Kadar Hemoglobin Pada Remaja Putri Anemia Di SMP N 19 Kota Bengkulu - A'yun, Nur Rosyidah Qurrota; Andriani, Lusi; Widiyanti, Desi (JURNAL BESUREK JIDAN, 2025)
Anemia is a condition where the number of red blood cells is lower than normal or an anemia disease, one of which is caused by a lack of iron consumption. This study aims to determine the effect of giving boiled free-range chicken eggs on increasing hemoglobin levels in anemic adolescent girls at SMP Negeri 19 Bengkulu City. This research uses a quasi-experimental design method, with Pre Test - Post Test with Control Group Design. The population in this study was 38 young women who experienced mild anemia, using a proportional sampling technique. Data were analyzed using univariate and bivariate analysis using the Paired Samples t-Test. The results of the study showed that there was an increase in hemoglobin levels before the intervention was given by giving free-range chicken boiled eggs, an average of 11.56 gr/dl, and after being given the intervention, the average hemoglobin level was 13.11 gr/dl with a difference of 1.55 gr/dl. There was a significant effect of giving boiled free-range chicken eggs on increasing hemoglobin levels (p = 0.000). It is hoped that the results of this research can increase support for teaching and medical staff in the School Health Unit (UKS) by providing health education about preventing anemia in adolescent girls, and by carrying out regular hemoglobin level checks.